2015
DOI: 10.1016/j.toxrep.2015.02.004
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of the cytotoxic and genotoxic potentials of zinc oxide and titanium dioxide nanoparticles

Abstract: Nanoparticles (NPs) of zinc oxide (ZnO) and titanium dioxide (TiO2) are receiving increasing attention due to their widespread applications. The aim of this study was to evaluate the toxic effect of ZnO and TiO2 NPs at different concentrations (50, 100, 250 and 500 ppm) and compare them with their respective salts using a battery of cytotoxicity, and genotoxicity parameters. To evaluate cytotoxicity, we have used human erythrocytes and for genotoxic studies human lymphocytes have been used as in vitro model sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
76
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 162 publications
(88 citation statements)
references
References 55 publications
5
76
0
1
Order By: Relevance
“…As mentioned above, they found that toxic superoxide radical formation by ZnO nanoparticles was much more than ZnSO 4 . In addition, they observed a dosedependent increase in activity of erythrocyte SOD (46). These data completely match those reported here.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…As mentioned above, they found that toxic superoxide radical formation by ZnO nanoparticles was much more than ZnSO 4 . In addition, they observed a dosedependent increase in activity of erythrocyte SOD (46). These data completely match those reported here.…”
Section: Discussionsupporting
confidence: 89%
“…However, based on their findings, it cannot be generalized that nanoparticles are always more toxic than micrometer particles (45). Further, in a study, the ability of ZnO nanoparticles in generation of different ROS was compared to their respective ionic form and results showed that ZnO nanoparticles hugely release ROS compared to their salt and consistently MDA production by ZnO nanoparticles was more than zinc sulfate (46). The mechanisms by which zinc protects against lipid peroxidation and ROS generation have not yet been completely elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the vast differences in their physico-chemical properties, primarily resultant from their differing synthesis methods, they are known to induce adverse effects in biological systems. NPs can interfere with cellular systems by the NPs interaction's with proteins, DNA, lipids, membrane, organelles, and biological fluids (Roiter et al 2008, Shang et al 2014, Khan et al 2015. Due to their reduced size (1-100 nm) and large surface area to volume ratio, they can easily cross cell membranes (Khan et al 2015) and further enter the bloodstream reaching different organs (Vishwakarma et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…NPs can interfere with cellular systems by the NPs interaction's with proteins, DNA, lipids, membrane, organelles, and biological fluids (Roiter et al 2008, Shang et al 2014, Khan et al 2015. Due to their reduced size (1-100 nm) and large surface area to volume ratio, they can easily cross cell membranes (Khan et al 2015) and further enter the bloodstream reaching different organs (Vishwakarma et al 2010). Their interactions with the culture medium or biological fluids have also been reported to be an important consideration for their toxicological evaluation due to the increased probability of aggregation upon dispersion in these environments, which is known to influence their cellular uptake with a subsequent impact on their toxicity (De Matteis 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation